Plastic Design of Steel Floor Beams - Hawes, William H. (Engineering Journal, 1979)
The potential for savings in material and improvement in performance which can be realized by use of plastic design for continuous floor beams, warrants increased attention from fabricators and designers. Various facets of application of this concept will be discussed. The top flanges of floor beams are generally the same nominal elevation as those of the girders. Consequently, whether framing to girders or to columns, the beams could be spliced at a plastic hinge point. Such an arrangement, utilizing A36 steel beams, is assumed in this paper. Items such as reduced restraint for end spans, deductions for bolt holes, and problems in developing full plastic moment capacity at connections are details which require attention if the full efficiency of plastic design is to be achieved. Some compromises, as discussed below, are desirable to avoid overcomplicating the fabrication and erection, in the attempt to save a last increment of beam weight. From the foregoing, it is evident that plastic design in general, and plastic-composite design in particular, does reduce the cost and improve the performance of steel beam floor systems. The continuous connections need not be complicated. Using the M-Seat as a base detail, a means for specifying and detailing connections has been presented, which allows the fabricator and erector to use a method best suiting their fabrication and erection practices and capabilities, while adhering to sound standards for performance and integrity.